PENERAPAN MODEL PASA (PICTURE AND STUDENT ACTIVE) UNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN IPS KELAS VIII SMP MUHAMMADIYAH 2 PURWOHARJO TAHUN AJARAN 2022/2023 - Kharisma Mellanio Putra; Mahfud; Sahru Romadloni; I Kadek Yudiana (Yayasan Nusantara Hasana Berdikari, 2023)
The PASA learning model (picture and student active) is active learning using pictures. This study aims to determine: (1) Learning Model; (2) Learning outcomes; (3) IPS Learning. This research uses classroom action research methods, so the data used are (1) Qualitative Data, (2) Quantitative Data. Based on the results of observations at school, it is known that the delivery of material during learning by social studies teachers still uses conventional models. Students just sit and listen to the teacher explaining the material, after that work on the LKS. The class atmosphere becomes inactive, students tend to get bored quickly and are lazy to learn so that student scores are low. After implementing the PASA model, there was an increase in learning outcomes based on the results of the students' test scores increasing. Delivering material using the PASA learning model with power point slide media and providing motivation makes students more enthusiastic about learning. The results of this study can be summarized as follows: 1) The results of the pre-cycle reached 69.35% of students who completed the KKM and 30.65% of students who did not complete the KKM, 2) The results of the first cycle of student learning outcomes who completed the KKM reached 70.74 % and the learning outcomes of students who did not complete the KKM reached 29.26%, 3) The results of the second cycle increased and reached the classical completeness target of 87.13% of students who completed the KKM and the learning outcomes of students who did not complete the KKM reached 12.87%.